2021
DOI: 10.1111/maec.12647
|View full text |Cite
|
Sign up to set email alerts
|

Cryptofauna associated with rhodoliths: Diversity is species‐specific and influenced by habitat

Abstract: Rhodolith beds provide heterogeneous and complex threedimensional habitats, providing ecosystem services disproportionate to their size (Lundquist et al., 2017), and meeting the definition of foundation species provided by Dayton (1972). Rhodoliths, or maerl, are calcified red algae that are free-living (Foster, 2001;Riosmena-Rodríguez et al., 2017) and are found globally from high to low latitudes (McCoy & Kamenos, 2015). Their morphological complexity and the interstitial spaces they provide serve as a refug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Likewise, a high variety of rhodolith-bed associated infauna and epifauna (e.g., sponges, nematodes, polychaetes, crustaceans, molluscs, and echinoderms) has been found wherever in the world studies have taken place (Hall-Spencer, 1998;Steller et al, 2003;Sciberras et al, 2009;Neill et al, 2015;Bassi et al, 2020;Navarro-Mayoral et al, 2020;Sánchez-Latorre et al, 2020;Veras et al, 2020;Stelzer et al, 2021;Voerman et al, 2022a). Furthermore, Méndez Trejo et al (2021) found species-and location-specific differences in the cryptofauna associated with two different rhodolith-forming species. Last, but not least, in contrast to other coastal habitats, such as seagrass meadows and kelp forests, rhodolith beds are usually formed by several different species of coralline algae, belonging to different families and even orders.…”
Section: Biological Diversitymentioning
confidence: 97%
See 1 more Smart Citation
“…Likewise, a high variety of rhodolith-bed associated infauna and epifauna (e.g., sponges, nematodes, polychaetes, crustaceans, molluscs, and echinoderms) has been found wherever in the world studies have taken place (Hall-Spencer, 1998;Steller et al, 2003;Sciberras et al, 2009;Neill et al, 2015;Bassi et al, 2020;Navarro-Mayoral et al, 2020;Sánchez-Latorre et al, 2020;Veras et al, 2020;Stelzer et al, 2021;Voerman et al, 2022a). Furthermore, Méndez Trejo et al (2021) found species-and location-specific differences in the cryptofauna associated with two different rhodolith-forming species. Last, but not least, in contrast to other coastal habitats, such as seagrass meadows and kelp forests, rhodolith beds are usually formed by several different species of coralline algae, belonging to different families and even orders.…”
Section: Biological Diversitymentioning
confidence: 97%
“…During the last five years, new discoveries have been reported for the Mediterranean (e.g., Bracchi et al, 2019Bracchi et al, , 2022Rendina et al, 2020;del Rio et al, 2022), the Macaronesia and São Tomé and Principe region (Rebelo et al, 2018(Rebelo et al, , 2022Otero-Ferrer et al, 2020a,b;Ribeiro and Neves, 2020;Neves et al, 2021;Cosme de Esteban et al, 2022), South Africa (Adams et al, 2020), the Western Indian Ocean (Ramah et al, 2021), Australia (Harvey et al, 2016), India (Sreeraj et al, 2018), Korea (Jeong et al, 2020), Brazil (Pereira-Filho et al, 2019Negrão et al 2021), and Alaska (Ward et al, 2021). Furthermore, the growing number of new, cryptic and endemic taxa being discovered in rhodolith beds indicates that much of their biodiversity is still unknown (e.g., Santos et al, 2016;Coutinho et al, 2021;Méndez Trejo et al, 2021;Senna et al, 2021;Sissini et al, 2022). Recent studies suggest that rhodolith beds may also act as seedbanks for recovering ecosystems, and as refugia for ecosystem resilience following acute (Fredericq et al, 2019) or chronic (Voerman et al, 2022a) environmental stress.…”
Section: Introductionmentioning
confidence: 99%
“…Complicating matters is the fact that the ecological roles played by coralline algae have been shown to be species‐specific (e.g. Villas Bôas & Figueiredo, 2004, O'Leary et al., 2017, Méndez Trejo et al., 2021), and coralline algal species can be difficult to identify morphologically (Hind et al., 2014; Twist et al., 2020). Moreover, ongoing molecular work has revealed many cryptic species with far greater diversity than previously thought in this group of algae (e.g., Hind & Saunders, 2013; Mills et al., 2022; Twist et al., 2019), and the importance of coralline algal diversity in key ecological processes remains unclear (Hind et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Scientific studies have identified a relationship between rhodolith morphological complexity and the associated biodiversity, evidencing that the diversity of cryptofauna is related to thallus size, growth form and structural complexity (Kamenos et al 2004;Steller et al 2003;Figueiredo et al 2007). In particular, it has been demonstrated that higher cryptofauna diversity is associated with highly branched forms of rhodoliths (Steller et al 2003;Foster et al 2007;Meihoub-Berlandi et al 2012;Méndez-Trejo et al 2021). Additionally, it has been observed that highdensity of rhodoliths harbor higher epibenthic and infaunal richness (Veras et al 2020), while larger sizes of rhodoliths seem to facilitate reproduction and feeding in fishes and invertebrates (Steller et al 2003;Gagnon et al 2012).…”
Section: Introductionmentioning
confidence: 99%